Penerapan Sistem Informasi Manajemen Untuk Meningkatkan Efektivitas Pelayanan Administrasi Desa Dahana Bawodesolo - Bryan Forman Zendrato; Eliagus Telaumbanua; Peringatan Harefa; Heseziduhu Lase (Lembaga Pengembangan Kinerja Dosen, 2025)
The era of globalization has had a significant impact on various aspects of life, including in the field of village government which is required to be able to provide effective and efficient public services. Advances in information technology have also encouraged the importance of implementing Management Information Systems (SIM) as an instrument for improving organizational performance, including in the implementation of village government administration. This research aims to analyze the implementation of the Village Information System (SID) through the SIKS-NG application in increasing the effectiveness of administrative services in Dahana Bawodesolo Village. The research method used is descriptive with a qualitative approach, which is supported by observations and interviews with village officials and the community. Preliminary results show that even though the implementation of SID has been implemented, its use is still not optimal due to low public understanding and limited supporting resources, such as technological infrastructure and user competence. This research uses Davis' information management theory and the organizational effectiveness approach as the basis for analysis. It is hoped that this research can contribute to developing strategies for improving information technology-based public services at the village government level and provide an overview for policy makers in strengthening human resource capacity and village digital infrastructure. The novelty of this research lies in its focus on optimizing the use of the SIKS-NG application as part of a village information system in the context of village government administration services in the digital era.